Developing Turkish EFL Students' Metacognitive Awareness and Listening Comprehension Skills Through Process-Based Instruction - Demirel Yılmaz, Ezgi (İstanbul Sabahattin Zaim Üniversitesi, 2024)
In this study the impact of a metacognitive, process-based instruction on metacognitive awareness and listening comprehension skills of Turkish EFL students was analyzed. Additionally, the study also investigated the participants’ attitude towards the implementation of process-based instruction in listening lessons. The study adopted a similar methodology to the study of Vandergrift and Tafaghodtari (2010). In total, 44 preparatory school students (N=21 control, N=23 experimental) took part in the study in Istanbul, Türkiye. For the experimental group, process based listening instruction was implemented whereas for the control group proceeded their regular lessons. The treatment process lasted for 5 weeks, two sessions each week (10 sessions in total). Quantitative data were collected through the Metacognitive Awareness Listening Questionnaire (MALQ) (Vandergrift et al. 2006) and a TOEFL listening test administered as pre-and post-tests. Qualitative data were collected through a focus group interview and the researcher’s reflective field notes. Research findings revealed that the disparity between the experimental and the control groups were statistically significant with regard to metacognitive awareness and listening comprehension performance, and raising students’ metacognitive awareness enhanced their listening comprehension. The results coincidentally indicated that the participants expressed a favorable attitude to the usage of process-based instruction for listening lessons and the majority of the students recommended its further implementation.

Bu çalışma, üst bilişsel, sürece dayalı öğretimin yabancı dil olarak İngilizce öğrenen Türk öğrencilerin üst bilişsel farkındalığı ve dinleme-anlama becerileri üzerine etkisini incelemiştir. Ayrıca, bu çalışma katılımcıların dinleme derslerinde sürece dayalı öğretimin uygulanmasına yönelik tutumu da araştırmıştır. Bu çalışma Vandergrift ve Tafaghodtari’nin (2010) yaptığı araştırmaya benzer bir metodoloji izlemektedir. İstanbul, Türkiye’de yer alan bir vakıf üniversitesinin hazırlık okulunda eğitim gören toplam 44 öğrenci (N=21 kontrol grup, N=23 deneysel grup) çalışmaya katılmıştır. Deneysel grup sürece dayalı dinleme öğretimi alırken kontrol grubu geleneksel öğretim ile derslerine devam etmiştir. Uygulama 5 hafta sürmüş ve haftada ikişer kez yapılan toplamda 10 oturumdan oluşmuştur. Nicel veriler, Üst Bilişsel Dinleme Anketi (Vandergrift vd., 2006) ve bir TOEFL dinleme sınavı ön ve son testleri; nitel veriler ise bir odak grup görüşmesi ve öğretmenin alan notları yoluyla toplanmıştır. Araştırmanın bulguları deneysel ve kontrol grupları arasında üst bilişsel farkındalık ve dinleme-anlama performansı açısından istatistiksel bağlamda anlam ifade eden bir farklılık olduğunu ve öğrencilerin üst bilişsel farkındalığını artırmanın dinlemeanlamayı geliştirdiğini ortaya koymuştur. Sonuç aynı zamanda katılımcıların dinleme derslerinde sürece dayalı öğretim kullanımına olumlu bir tutum sergilediklerini ve çoğunluğunun bu öğretim yönetiminin ileride de uygulanmasını tavsiye ettiklerini göstermiştir.
Yabancı Dil Olarak İngilizce Öğrenen Türk Öğrencilerin Üstbilişsel Farkındalığının ve Dinleme-Anlama Becerilerinin Süreç Temelli Öğretim Yoluyla Geliştirilmesi
Keywords: Process-Based Instruction; Metacognition; Metacognitive Awareness; Listening Comprehension; Metacognitive Instruction; Sürece Dayalı Öğretim; Üst Biliş; Üst Bilişsel Farkındalık; Dinleme Anlama; Üst Bilişsel Öğretim